Agricultural knowledge and information system on tea farming in Vietnam : implications for strengthening the extension service - Kieu Thi Thu, Huong; Justus Liebig University Giessen (My University, 2014)
Tea plays an important role in improving income and generating employment in the northern uplands of Vietnam. However, the tea sector is reportedly performing below its potential: low yields and productivity, and low product quality. Among the major problems affecting tea production is the limited access of tea producers to information both in production and marketing; low level of connections between actors in agricultural extension, researchers and the farmers themselves.This research tries to analyze the situation by using the Agricultural Knowledge and Information (AKIS) perspective to understand the knowledge system of the tea sector. The Parasuraman Model of quality service was used to identify the gaps which constrain the contribution of the extension system and to suggest what can be done to strengthen the extension service for effective contribution to the tea sector.Results show that the extension service, with top - down approach, operates their activities based on the agendas imposed from higher level of management. New technologies transferring to farmers were conducted by based on the viewpoints of researchers and following the orientation of government s development, not the farmers in local areas. ). Trainings provided by extension are normally too much theory and not satisfied by the farmers. The tea extension group in Thai Nguyen (established in 2001) shows many weaknesses in approaching farmers because they lack training in extension skills and methods. The tea extensionists admitted that their professional knowledge about tea was also limited. They respond to large areas with a high number of farmers cultivating small-sized farms. The limitations of the extension service result in a set of gaps preventing their contribution to the tea sector: (1) difference between farmer expectations and perceived needs of farmers by extension service. (2) Difference between perceived needs of farmers by extension service and the application in their service strategies. (3) Discrepancy between service specialization and the actual rendering of the service. This GAP existed due to the lack of quality of the extension staff. (4) Divergence between extension service delivery and communication with the customer. Farmers become inactive and have no voice in expressing their needs. Feedback about extension program delivery to farmers is also not considered. (5) Difference between the expectation of farmers and their perceptions on actual rendering of the extension service. Results from interviewing different farmer groups show that there are many differences between farmers expectation and the actual rendering of the extension service. Farmers commented that the extension activities are in the form of tokenism and do not consider the real needs of the farmers.
Keywords: ddc:630